Pengaruh Perputaran Kas dan Perputaran Piutang terhadap Profitabilitas Pada UMKM di Kota Pariaman - Mexano Hans Gery; Nichy Oktaviani; Henny Wati; Sudirman (SAFE-Network, 2024)
This research aims to determine the influence of cash turnover and accounts receivable turnover on profitability in MSMEs in Pariaman City. The background to this title is that many MSMEs in Pariaman City do not have bookkeeping that is in accordance with accounting standards so that the level of profit obtained cannot be calculated in detail. collect This research uses a quantitative type of research. The data taken is secondary data by conducting direct interviews with business owners, by preparing questions and looking at bookkeeping records made by MSME actors. This research carries out classical assumption tests, hypothesis testing using SPSS version 21. The results of the research state that looking at the results of the tests that have been carried out proves that both variables partially and simultaneously have a significant effect on profitability and it can also be seen that the Adjusted R Square is 0.435. This means that 43.5% of the Profitability variable is influenced by cash turnover and the remaining 56.5% of receivables turnover is influenced by other variables outside of this research variable.